Analisis Kemampuan Mahasiswa PGSD FIP UNM dalam Mengembangkan Rencana Pelaksanaan Pembelajaran PKn Berbasis Kurikulum 2013 - Ritha Tuken (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The problem in this research is that there are students who sometimes experience problems in developing learning implementation plans on Civics content. The method in this research is descriptive research with a quantitative approach. The results showed that: 60% of students had good ability in compiling, 20% of students had very good ability, 15% of students had sufficient ability and 5% of students with less ability in compiling an Implementation Plan for Citizenship Education Learning in Elementary Schools. Meanwhile, in terms of student abilities in developing lesson plans components consisting of developing indicators, objectives, materials and learning assessments, they are in the good category.